Development of multiplex PCR for the detection of total coliform bacteria for Escherichia coli and Clostridium perfringens in drinking water - Suwalee Tantawiwat (2018)
Multiplex PCR amplification of lacZ, uidA and plc genes was developed for the simultaneous detection of total coliform bacteria for Escherichia coli and Clostridium perfringens, in drinking water. Detection by agarose gel electrophoresis yielded a band of 876 bp for the lacZ gene of all coliform bacteria; a band of 147 bp for the uidA gene and a band of 876 bp for the lacZ gene of all strains of E. coli; a band of 280 bp for the plc gene for all strains of C. perfringens; and a negative result for all three genes when tested with other bacteria. The detection limit was 100 pg for E. coli and C. perfringens, and 1 ng for coliform bacteria when measured with purified DNA. This assay was applied to the detection of these bacteria in spiked water samples. Spiked water samples with 0-1,000 CFU/ml of coliform bacteria and/or E. coli and/or C. perfringens were detected by this multiplex PCR after a pre-enrichment step to increase the sensitivity and to ensure that the detection was based on the presence of cultivable bacteria. The result of bacterial detection from the multiplex PCR was comparable with that of a standard plate count on selective medium (p=0.62). When using standard plate counts as a gold standard, the sensitivity for this test was 99.1 % (95% CI 95.33, 99.98) and the specificity was 90.9 % (95% CI 75.67, 98.08). Multiplex PCR amplification with a pre-enrichment step was shown to be an effective, sensitive and rapid method for the simultaneous detection of these three microbiological parameters in drinking water.